2017
DOI: 10.3389/fphys.2017.00262
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary Patterns, Physical Activity, and Cardiorespiratory Fitness in Association to Glycemic Control in Type 2 Diabetes Patients

Abstract: Background: Sedentary behavior has been considered an independent risk factor for type-2 diabetes (T2D), with a negative impact on several physiological outcomes, whereas breaks in sedentary time (BST) have been proposed as a viable solution to mitigate some of these effects. However, little is known about the independent associations of sedentary pursuits, physical activity, and cardiorespiratory fitness (CRF) variables with glycemic control. We investigated the independent associations of total sedentary tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 63 publications
4
35
0
Order By: Relevance
“…Nonetheless, lower fasting glucose and the dawn phenomenon in response to Condition 3 could reflect improved insulin sensitivity . Observational and experimental studies have already reported that breaks in sedentary time improve insulin homeostasis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, lower fasting glucose and the dawn phenomenon in response to Condition 3 could reflect improved insulin sensitivity . Observational and experimental studies have already reported that breaks in sedentary time improve insulin homeostasis .…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that sedentary time is associated with high fasting glucose, insulin resistance and metabolic risk profile . By contrast, breaks in sedentary time have a beneficial effect on metabolic risk profile and postprandial glucose, and this beneficial effect might extend to basal glucose control .…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on the SB of T2DM patients found that SB is associated with abnormal glucose metabolism and metabolic risk factors and concluded that SB has a high correlation with the risk of cardiovascular disease mortality [11][12][13]. A study reported that SB was significantly correlated with body mass index (BMI) and waist circumference [14], and another study emphasized that the number of breaks in sedentary time (ST) should be increased to prevent central obesity [15].…”
Section: Introductionmentioning
confidence: 99%
“…13.3%) were in their 40's, 47 (39.3%) in 50's, 43 (35.8%) in 60's, 13 (10.8%) in 70's, and one (0.8%) in 80's. The mean age of study subjects was 59.3 years.…”
mentioning
confidence: 96%
“…As for metabolic function, sedentary behavior causes the deterioration of glycemic control [5] and an increased risk of type 2 diabetes (T2D) [6]. Previous research showed that an increase in the amount of time spent in daily sedentary behavior caused poor glycemic control in T2D patients [7]. On the other hand, in individuals with type 1 diabetes (T1D), the association between sedentary behavior and health outcomes is unclear.…”
Section: Introductionmentioning
confidence: 99%